Childhood‐onset progressive dystonia associated with pathogenic truncating variants in CHD8. Issue 10 (20th August 2021) - Doummar, Diane; Treven, Marco; Qebibo, Leila; Devos, David; Ghoumid, Jamal; Ravelli, Claudia; Kranz, Gottfried; Krenn, Martin; Demailly, Diane; Cif, Laura; Davion, Jean‐Baptiste; Zimprich, Fritz; et al.
Abstract: Originally described as a risk factor for autism, CHD8 loss‐of‐function variants have recently been associated with a wider spectrum of neurodevelopmental abnormalities. We further expand the CHD8 ‐related phenotype with the description of two unrelated patients who presented with childhood‐onset progressive dystonia. Whole‐exome sequencing conducted in two independent laboratories revealed a CHD8 nonsense variant in one patient and a frameshift variant in the second. The patients had strongly overlapping phenotypes characterized by generalized dystonia with mild‐to‐moderate neurodevelopmental comorbidity. Deep brain stimulation led to clinical improvement in both cases. We suggest that CHD8 should be added to the growing list of neurodevelopmental disorder‐associated genes whose mutations can also result in dystonia‐dominant phenotypes.